Examining Students’ Perceptions of Indonesian High School Students on the Use of TikTok in Learning English - Ika Apriani Fata; Lathifah M. Nur; Andira Riski Alya (Universitas Islam Negeri Walisongo Semarang, 2023)
With the availability of mobile devices and Web 2.0 technologies, various networking apps have become essential to English language learning (ELL). TikTok, a global app similar to YouTube, WhatsApp, Instagram, and Twitter, is becoming increasingly popular. TikTok is a video-sharing app that allows users to produce and share content while discovering material from other users. TikTok has yet to be thoroughly researched for educational purposes. However, some research suggests that social media can help language learners. This study evaluated Islamic school students' perspectives on using TikTok to learn English to enhance four English skills. In this study, 55 high school students from an Islamic country participated in an online quantitative research survey. The information was gathered using a Google Forms questionnaire. According to the research, students were enthusiastic about utilizing TikTok as a visual aid in enhancing their English skills. Writing was discovered to be the least likely of the four English skills to develop using TikTok Apps. Besides, students also stated a high preference for watching native English channels rather than local channels when learning English. As a result, TikTok has the potential to affect pupils' English proficiency positively. As a result, students and teachers can mix social networking apps to enhance English teaching and learning. Further research may be performed to look at students' voices, in the future teachers' views, and an experimental classroom design.